Bilayer Membrane Composed of Mineralized Collagen and Chitosan Cast Film Coated With Berberine-Loaded PCL/PVP Electrospun Nanofiber Promotes Bone Regeneration - Zhang, Yuhan; Wang, Ting; Li, Juan; Cui, Xiaoming; Jiang, Mingxia; Zhang, Mogen; Wang, Xiaoli; Zhang, Weifen; Liu, Zhijun (Frontiers in Bioengineering and Biotechnology, 2021)
The study involved developing a bilayer membrane that provides good bioactivity and mechanical characteristics by combining mineralized collagen (MC) powder and berberine. The bilayer membrane was prepared via coating Polycaprolactone (PCL)/Polyvinylpyrrolidone (PVP) nanofibers which load with berberine (BER) on mineralized collagen (MC) and chitosan (CS) cast film. Electrospinning nanofibers membrane has a three-dimensional structure, the fibers are uniform diameter, and have improved hydrophilicity. The bilayer membrane showed suitable attachment and proliferation of osteoblasts, superior mechanical properties, and promoted bone regeneration in rats’ femur with the best effect. This work demonstrates a promising way to address the regeneration of bone defects by using the BER@PCL/PVP-MC/CS bilayer membrane.